Highly efficient cold-white light emission in a [Au2CuCl2(P∩N)2]PF6 type salt. Issue 11 (17th February 2017) - Hobbollahi, Elnaz; List, Manuela; Hupp, Benjamin; Mohr, Fabian; Berger, Raphael J. F.; Steffen, Andreas; Monkowius, Uwe
Abstract : The metallophilic interactions in the cluster [Au2 CuCl2 (P∩N)2 ]PF6 give rise to very efficient cold-white light emission. Abstract : In the trinuclear, heterometallic cluster compound [Au2 CuCl2 (P∩N)2 ]PF6 metallophilic interactions give rise to very efficient cold-white light emission as a result of at least two thermally non-equilibrated emissive triplet states (one of mainly Cu → py and the other of Au → py character, respectively) with exceptional spin–orbit coupling and short emission lifetimes, which are competitive to Pt II - and Ir III -based emitters.